Književnopovijesni modus procedendi Julija Benešića u zbirci Poljska lirika - Rogić Musa, Tea (Przekłady Literatur Słowiańskich, 2018)
Literary-Historic Modus Procedendi of Julije Benešić in the Collection Polish Lyricism During his entire work in philology Julije Benešić had systematically translated two types of texts: masterpieces of canonical Polish authors, which he considered to be his most important work as an author and as a cultural mediator, however he also translated a series of shorter works of authors who were not famous in Croatia, which he undertook out of his polonophilic tendencies. In his work as a translator, Polish Lyricism, a chrestomathy spanning five centuries of Polish literature, holds a special place. In the article we will try to come to a conclusion to what extent were Benešić’s choice as a translator and his work as a historian successful, i.e. did they correspond with topics important to the entire Croatian literary and social environment of his, interwar, period, as well as our own period. KEY WORDS: Julije Benešić, Poljska lirika, Današnja Poljska, Croatian-Polish Literary Relations